The Study of Fraud in Financial Institutions (Analysis of the Theory of Fraud Triangle in Perspective of Islamic Sharia) - N. Nadhirin; H. Husnurrosyidah (IQTISHADIA, 2018)
This research aims to (1) reveal the fraud practices and the factors that caused it, (2) understand and analyze the practices of fraud in the perspective of the theory of triangle of fraud and fraud in the Islamic perspective (3) find the pattern prevention of practice fraud. This study used a qualitative approach. Engineering data collection with interviews, observation and documentation. The location of this research on BPR Mandiri Arta Abadi, Semarang. The subject of this research include leadership of the BPR, customers and some employees. The validity of the data was tested with triangulation, include angulasi techniques, resources and time. Data were analyzed with the interactive silkus technique, namely, collecting, reducing, displaying and verifying. The research found that fraud was done by because many factors, both factors that is internal or external. Internally the offender committing fraud because the urge to want to earn more income outside official income received. A sense of responsibility both morally and awareness religions are less well encourage perpetrators to commit fraud. The academic level of education principals, pushing data to rationalize, and make a decision. The external pressure that is encouraging the perpetrators of fraud are due to the pressure of the needs and desires of your family and those near loved as well as supply of goods and services that encourage actors to do the fraud at work. Approach to fraud from the perspective of Sharia and triangle, resulting in a more comprehensive understanding of fraud, academic, ethical and transcendental. So with a comprehensive understanding of this, is able to prevent acts of fraud in financial institutions.